"Hold on! I'll Just Google It!": Critical Conversations Regarding Dimensions of Diversity in a School Leadership Preparation Program. (March 2018) - Boske, Christa; Elue, Chinasa
This case outlines a dilemma encountered by faculty and graduate assistants in a K-12 educational administration graduate program. The case offers a detailed illustration of tensions arising when faculty were asked to increase "diversity" within their program. Faculty uncover disrupting institutional systems of domination that often play a significant role in understanding how to prepare leaders to serve in authentic and meaningful ways. Implications for the development of social justice–oriented school leaders included an intentional examination of these issues.